Too Much Programming Too Soon? - Guzdial, Mark; Robertson, Judy (Communications of the ACM, 2010)
The author discusses problems with teaching introductory computer science. It is suggested that the common practice of asking students to engage in programming activities that simulate the problems of professionals in the field may not be the most effective teaching method. A research paper titled "Why Minimal Guidance During Instruction Does Not Work: An Analysis of the Failure of Constructivist, Discovery, Problem-Based, Experimental, and Inquiry-Based Teaching," by Kirschner, Sweller, and Clark is cited as finding evidence that the minimal-guidance technique is not productive.